SAACCESS (SIMPAN ARSIP DENGAN ACCESS) APPLICATION DEVELOPMENT AT 11TH STATE SENIOR HIGH SCHOOL SURABAYA - Aris Jaka Purnama; Brillian Rosy; Meylia Elizabeth Ranu; Novi Trisnawati (Journal of Social and Economics Research, 2023)
Archives are the center of memory in every activity in the office. Archives function as a memory center, proof of the existence of the institution, and for the benefit of other institutions. Therefore, there must be good management or management of archives from creation to shrinkage. The main obstacle is the decreasing physical letter storage space, but it’s not possible to build a special building for physical letter storage space. Using the type of research with R&D (Research and Development) and prototype development research methods. Development of this archival application uses a Microsoft Access-based application. This research goes through a research procedure starting with information gathering, designing the product quickly, building a prototype, and the final step is that the application is ready to use with an evaluation that has been carried out by experts. The subject is 2 peoples from 11th Senior High School Surabaya administration staff. The trial was conducted in December 2023 and January 2024. The application feasibility results based on material expert validators and media expert validators get a score of 96%. While the results of application feasibility based on administrative staff get a score of 88.8%, which shows the interpretation of “Very Feasible”. The development of Microsoft Access-based digital archiving applications uses a prototype development model. The SAAccess application received a feasibility score of 96% from both the material expert validator and the software developer. SAAccess also received a score of 88.8% from the administrative staff of 11th Senior High School Surabaya. It can be concluded that SAAccess is effectively used to manage letters in 11th Senior High School Surabaya digitally.